Acral Lentiginous Melanoma: A Case Control Study and Guidelines Update - Christoforos Kosmidis; Christoforos Efthimiadis; Georgios Anthimidis; Marios Grigoriou; Kalliopi Vasiliadou; Georgia Ioannidou; Fotini Makedou; Sofia Baka (Case Reports in Medicine)
Background. Malignant melanoma incidence is increasing dramatically. We report herein a case of the rarest acral lentiginous type. Case Report. A 58-year-old man presented with a melanoma resembling lesion over the sole of his right foot, measuring 15–20 mm in diameter. An excisional biopsy with a narrow (2 mm) margin of surrounding skin was obtained. Histological findings were consistent with a diagnosis of acral lentiginous melanoma. Sentinel lymph node biopsy was also performed and micrometastases were not identified in frozen-section examination. According to the AJCC system, the tumor stage was IB (T2aN0M0). A wide local excision of the biopsy scar with a margin of 2 cm was performed. A split-thickness thick skin graft was used to reconstruct the excisional defect. During an 18-month followup, no local or distant recurrence has been observed. This paper aims to extract an updated rational approach to the management of this disease out of an enormous body of knowledge.